Roxas : the story of a great Filipino and of the political era in which he lived - Lichauco, Marcial P. (Manila : Kiko Printing Press, 1952)
When Manuel Roxas met his untimely end in Clark Field that tragic afternoon of April 15, 1948, he had already occupied more important positions in our government than any other Filipino had ever held before him.
Keywords: ROXAS, MAUEL A., 1892-1948; ROXAS, MAUEL A., 1892-1948 -- FAMILY; ROXAS, MAUEL A., 1892-1948 -- POLITICAL CAREER